The Role of Tax Officials in Mitigating Company’s Tax Obstacles - Asrindah, Disa; Atmoko, Alfriadi Dwi (Faculty of Economics and Business, Hasanuddin University, 2024)
This study aims to examine the role of tax official in mitigating the positive relation between firm’s informal payment on tax obstacle. As the general discourses in tax avoidance, regulation, and compliance, the role of tax official is still had limited attention. In this regard, the examination based on the data of 229 firms from the World Bank Enterprise Survey 2019, specifically in two countries (i.e., Estonia and Latvia) which are listed as the top two countries with the highest International Tax Competitiveness Index. Accordingly, this study found that in the country well-established tax management, firm’s informal payment is positively affecting the level of its tax obstacle, while professionality and transparency of tax official is reporting a negative effect. Interactionally, tax official is weakening the positive effect of informal payment on tax obstacle. In general, this denote and provide evidence for the important role of professional and transparent tax official in the tax management. Several discussions further been elaborated in both theoretical and practical to enrich the topic of tax management.